Interactive Effects of Light-Sources, Photoperiod and Strain on Blood Physiological Variables of Broilers Grown to Heavy Weight - Olanrewaju , H.A.; Purswell, J.L.; Collier, S.D.; Branton, S.L. (International Journal of Poultry Science, 2020)
Objective: Effects of light sources, photoperiods and strains on blood physiological variables of broilers grown to heavy weights (>3 kg) were investigated in 2 trials. Materials and Methods: The experimental design was a 4×2×2 factorial consisting of 4 light sources [incandescent (ICD, standard), compact fluorescent (CFL), neutral LED (Neutral-LED) and cool poultry specific LED (Cool-PS-LED)], 2 photoperiods (Regular/intermittent [2L:2D] and Short [8L:16D] and 2 strains (A, B). In each trial, 480 (240 males/240 females) 1-d-old chicks of each strain from different commercial hatcheries were equally and randomly distributed into 16 environmental-control rooms (30 males +30 females/room) at 50% RH. Each room was randomly assigned one of 16 treatments from 1-56 days of age. Birds were provided similar diets. Feed and water were provided ad libitum. Venous blood samples were collected on d 14, 28, 42 and 56 of age and analyzed immediately. Results: Light sources had significant (p